Multilayer structure, molded body, and method for producing molded body

JP7640460B2Active Publication Date: 2025-03-05KURARAY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021548946
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-24
Filing Date
2020-09-24
Publication Date
2025-03-05
Estimated Expiration
2040-09-24

Smart Images

  • Figure 0007640460000006
    Figure 0007640460000006
  • Figure 0007640460000001
    Figure 0007640460000001
  • Figure 0007640460000002
    Figure 0007640460000002
Patent Text Reader

Abstract

Provided are: a multi-layer structure having excellent solvent resistance while maintaining gas barrier properties and flex resistance; a molded article provided with said multi-layer structure; and a method for producing said molded article. The multi-layer structure is provided with: one or more gas barrier layers (A) each containing an ethylene-vinyl alcohol copolymer (a1) and a thermoplastic resin (a2) having a functional group capable of reacting with the ethylene-vinyl alcohol copolymer (a1); and one or more polyurethane layers (B) each containing a thermoplastic polyurethane (b). The content of the thermoplastic resin (a2) with respect to a total of 100 parts by mass of the ethylene-vinyl alcohol copolymer (a1) and the thermoplastic resin (a2) is 0.1-30 parts by mass. At least one set of a gas barrier layer (A) and a polyurethane layer (B) are configured to be directly stacked one on another, and the total number of layers of the gas barrier layers (A) and the polyurethane layers (B) is 9-300.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multilayer structure, a molded article, and a method for producing a molded article. [Background technology]

[0002] Films using resins having gas barrier properties, such as ethylene-vinyl alcohol copolymers, are widely used in various applications, such as food and medical packaging materials. Recently, for the purpose of improving various performances, such as gas barrier properties, various multilayer structures have been proposed in which multiple resin layers, each of which has a thickness on the order of microns or submicrons, are laminated.

[0003] As a conventional multilayer structure in which multiple resin layers of such ethylene-vinyl alcohol copolymers are laminated, for example, Patent Document 1 describes a multilayer structure having a total of eight or more layers made of a resin composition containing a gas barrier resin such as an ethylene-vinyl alcohol copolymer and a layer made of a thermoplastic resin such as a thermoplastic polyurethane. Patent Document 1 describes that a multilayer structure excellent in interlayer adhesion, flex resistance, etc. can be provided by incorporating a metal salt into one of the adjacent resin layers. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2011 / 068105 Summary of the Invention [Problem to be solved by the invention]

[0005] The multilayer structure as described above may be used in applications where it is exposed to organic solvents such as methanol. In addition, when coloring the multilayer structure, it may be colored by immersing the multilayer structure in an organic solvent containing a colorant. However, in the multilayer structure having 8 or more layers described in Patent Document 1, when exposed to an organic solvent, some of the layers may peel off. Therefore, there is a demand for a multilayer structure that has excellent resistance to peeling even when exposed to an organic solvent while maintaining physical properties such as gas barrier properties and bending resistance due to the multilayer structure having 8 or more layers. It has been found that peeling when exposed to an organic solvent is a problem that is significantly observed only in multilayer structures with a large total number of layers.

[0006] The present invention has been made based on the above-mentioned circumstances, and an object of the present invention is to provide a multilayer structure that is excellent in solvent resistance while maintaining gas barrier properties and flex resistance, a molded article including such a multilayer structure, and a method for producing the molded article. [Means for solving the problem]

[0007] According to the present invention, the above object is achieved by: [1] A multilayer structure comprising a gas barrier layer (A) containing an ethylene-vinyl alcohol copolymer (a1) and a thermoplastic resin (a2) having a functional group capable of reacting with the ethylene-vinyl alcohol copolymer (a1), and a polyurethane layer (B) containing a thermoplastic polyurethane (b), wherein the content of the thermoplastic resin (a2) is 0.1 to 30 parts by mass per 100 parts by mass of the ethylene-vinyl alcohol copolymer (a1) and the thermoplastic resin (a2), and wherein at least one pair of the gas barrier layer (A) and the polyurethane layer (B) are directly laminated together, and the total number of the gas barrier layer (A) and the polyurethane layer (B) is 9 to 300; [2] The multilayer structure of [1], wherein the functional group of the thermoplastic resin (a2) is a carboxy group or a derivative thereof; [3] The multilayer structure of [1] or [2], wherein the acid value of the thermoplastic resin (a2) is 0.5 to 50 mgKOH / g; [4] The multilayer structure of any one of [1] to [3], wherein the thermoplastic resin (a2) is at least one selected from the group consisting of modified polyethylene, modified polypropylene, modified ethylene-vinyl acetate copolymer, and modified ethylene-ethyl acrylate copolymer; [5] The multilayer structure of any one of [1] to [4], wherein the ethylene unit content of the ethylene-vinyl alcohol copolymer (a1) is 20 mol % or more and 60 mol % or less; [6] The multilayer structure of any one of [1] to [5], wherein the gas barrier layer (A) further contains a higher fatty acid metal salt (a3); [7] The multilayer structure of any one of [1] to [6], in which gas barrier layers (A) and polyurethane layers (B) are laminated alternately; [8] The multilayer structure of [7], wherein the polyurethane layer (B) comprises a polyurethane layer (B1) having a gas barrier layer (A) directly laminated on both sides thereof, and a polyurethane layer (B2) having a gas barrier layer (A) directly laminated on only one side thereof. [9] The multilayer structure of [8], further comprising a protective layer (D) directly laminated to the polyurethane layer (B2), the protective layer (D) comprising a thermoplastic polyurethane (x).

[10] The multilayer structure of [9], wherein the protective layer (D) contains an ethylene-vinyl alcohol copolymer (y).

[11] The multilayer structure of [9] or

[10] , wherein the average thickness of each protective layer (D) is 300 μm or more and 800 μm or less.

[12] The multilayer structure of any of [1] to

[11] , wherein the outermost layer is a polyurethane layer (B);

[13] The multilayer structure of any one of [1] to

[12] , wherein the average thickness of each gas barrier layer (A) is 0.1 μm or more and 15 μm or less;

[14] The multilayer structure of any of [1] to

[13] , wherein the average thickness of each polyurethane layer (B) is 0.1 μm or more and 30 μm or less;

[15] The multilayer structure of any of [1] to

[14] , wherein the gas barrier layer (A) forms a phase-separated structure having a sea phase and an island phase, the sea phase containing an ethylene-vinyl alcohol copolymer (a1) and the island phase containing a thermoplastic resin (a2).

[16] The multilayer structure according to

[15] , further comprising a phase containing an ethylene-vinyl alcohol copolymer (a1) inside the island phase.

[17] A molded article having the multilayer structure according to any one of [1] to

[16] , wherein at least one of the gas barrier layer (A) and the polyurethane layer (B) contains a colorant;

[18] A method for producing a molded article, comprising a step of contacting the multilayer structure according to any one of [1] to

[16] with a treatment liquid containing an organic solvent;

[19] The method for producing a molded article according to

[18] , wherein the treatment liquid contains a colorant; This is achieved by providing Effect of the Invention

[0008] According to the present invention, it is possible to provide a multilayer structure that has excellent solvent resistance while maintaining gas barrier properties and flex resistance, and a product including the multilayer structure. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a TEM image of a cross section of layer A in the multilayer structure of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Multilayer structure> The multilayer structure of the present invention comprises a gas barrier layer (A) (hereinafter may be abbreviated as "layer A") containing an ethylene-vinyl alcohol copolymer (a1) (hereinafter may be abbreviated as "EVOH (a1)") and a thermoplastic resin (a2) having a functional group capable of reacting with EVOH (a1), and a polyurethane layer (B) (hereinafter may be abbreviated as "layer B") containing a thermoplastic polyurethane (b) (hereinafter may be abbreviated as "TPU (b)"). The content of the thermoplastic resin (a2) is 0.1 to 30 parts by mass per 100 parts by mass of the ethylene-vinyl alcohol copolymer (a1) and the thermoplastic resin (a2), and at least one pair of the gas barrier layer (A) and the polyurethane layer (B) is directly laminated together. The total number of the gas barrier layer (A) and the polyurethane layer (B) is 9 to 300. According to the present invention, a multilayer structure can be provided that includes at least one pair of A layer and B layer directly laminated together, the total number of A layers and B layers is 9 or more, and the A layer contains a specific amount of thermoplastic resin (a2), thereby maintaining high gas barrier properties and flex resistance obtained by the multilayer structure, while exhibiting excellent solvent resistance and excellent delamination resistance even when exposed to an organic solvent. In the present specification, the term "gas barrier properties" can be evaluated based on the measured oxygen permeability, and specifically, can be evaluated by the method described in the Examples.

[0011] The multilayer structure of the present invention may be composed of only layers A and B, or may have other resin layers other than layers A and B. The multilayer structure of the present invention may further have layers other than the resin layers. From the viewpoint of maintaining the gas barrier property after bending, it is preferable that the multilayer structure is composed of only layers A and B, but when other resin layers are provided, it is preferable that the other resin layers are the outermost layers.

[0012] The multilayer structure of the present invention includes a configuration in which at least one pair of A layer and B layer are directly laminated, preferably a configuration in which at least four pairs of A layer and B layer are directly laminated, and it is preferable that all A layers and B layers constituting the multilayer structure are directly laminated with any A layer or B layer. By having the above-mentioned direct lamination configuration, it is possible to achieve the effect of maintaining the gas barrier property after bending. In addition, from the viewpoint of maintaining the gas barrier property after bending, it is preferable that the A layer and the B layer are alternately laminated.

[0013] From the viewpoint of efficiently carrying out coextrusion, the multilayer structure of the present invention preferably has a symmetrical structure (e.g., layer B / layer A / layer B / layer A / layer B / layer A / layer B / layer A / layer B).

[0014] When the A layer and the B layer are alternately laminated, from the viewpoint of further suppressing the deterioration of the gas barrier property when bent, it is preferable that the B layer has a polyurethane layer (B1) (hereinafter sometimes abbreviated as "B1 layer") on both sides of which the A layer is directly laminated, and a polyurethane layer (B2) (hereinafter sometimes abbreviated as "B2 layer") on only one side of which the A layer is directly laminated. That is, it is preferable that at least one of the outermost layers in the alternately laminated portion of the A layer and the B layer is the B layer. At least one of the outermost layers in this alternately laminated portion is the B2 layer, and the other B layer is the B1 layer. Furthermore, it is more preferable that the B layer has two B2 layers. That is, it is more preferable that both of the outermost layers in the alternately laminated portion of the A layer and the B layer are the B layer.

[0015] When the B2 layer is provided, the multilayer structure of the present invention preferably includes a protective layer (D) (hereinafter sometimes abbreviated as "D layer") directly laminated on the B2 layer, from the viewpoint of further suppressing the deterioration of the gas barrier property when bent. The protective layer (D) is a layer containing thermoplastic polyurethane (x) (hereinafter sometimes abbreviated as "TPU (x)"), and preferably contains an ethylene-vinyl alcohol copolymer (y) (hereinafter sometimes abbreviated as "EVOH (y)"). Examples of the layer structure of the multilayer structure including the D layer include D layer / B2 layer / A layer / B1 layer / A layer / B1 layer / A layer / B1 layer / A layer / B2 layer / D layer. The D layer is preferably the outermost layer. The D layer may be provided only on one side, but is preferably provided on both sides. The multilayer structure of the present invention may be a structure consisting of only the A layer and the B layer, a structure consisting of only the A layer, the B layer, and the D layer, or a structure further having other resin layers.

[0016] The number of layers A constituting the multilayer structure of the present invention is preferably 4 or more, more preferably 6 or more, and even more preferably 8 or more. When the number of layers A is 4 or more, the gas barrier property after bending can be better maintained, which is preferable. On the other hand, the number of layers A may be 150 or less.

[0017] The number of layers of the B layer constituting the multilayer structure of the present invention is preferably 4 or more, more preferably 6 or more, and even more preferably 8 or more. When the number of layers of the B layer is 4 or more, the gas barrier property after bending can be better maintained, which is preferable. On the other hand, the number of layers of the B layer may be 150 or less.

[0018] The total number of layers A and layers B constituting the multilayer structure of the present invention is 9 or more, preferably 11 or more, more preferably 15 or more, even more preferably 25 or more, and particularly preferably 30 or more. On the other hand, the total number of layers A and layers B is 300 or less, preferably 200 or less, and more preferably 100 or less. The total number of layers of the multilayer structure is also preferably within the above range. By making the multilayer structure into such a multilayer structure, even if defects such as pinholes or cracks occur in one layer A due to bending, the other layers A can maintain gas barrier properties, and as a result, the properties such as gas barrier properties and durability of the multilayer structure as a whole can be improved.

[0019] In addition, problems related to solvent resistance, such as delamination when exposed to organic solvents, are particular problems that occur prominently in conventional multilayer structures with a large number of layers. This is thought to be because, when the number of layers is large, the effect of swelling of each layer by the solvent becomes large. In a multilayer structure having a total of 9 or more layers of A and B, by including a predetermined amount of thermoplastic resin (a2) in A layer, the advantage of having excellent solvent resistance can be enjoyed even in such a multilayer structure.

[0020] The average thickness of one layer of A is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. On the other hand, the average thickness of one layer of A is preferably 15 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, and particularly preferably 2 μm or less. When the average thickness of one layer of A is 0.1 μm or more, it is relatively easy to mold it with a uniform thickness, and gas barrier properties, durability, solvent resistance, etc. tend to be improved. On the other hand, when the average thickness of one layer of A is 15 μm or less, flexibility, etc. are increased, and as a result, durability, etc. are also increased, and delamination when exposed to organic solvents tends to be less likely to occur.

[0021] The average thickness of one B layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 1 μm or more, and particularly preferably 3 μm or more. On the other hand, the average thickness of one B layer is preferably 30 μm or less, more preferably 15 μm or less, even more preferably 10 μm or less, and particularly preferably 8 μm or less. When the average thickness of one B layer is 0.1 μm or more, it becomes relatively easy to mold it with a uniform thickness, and durability, solvent resistance, etc. tend to be improved. In addition, sufficient flexibility is easily expressed. On the other hand, when the average thickness of one B layer is 30 μm or less, interlayer adhesion and gas barrier properties are improved, and delamination when exposed to an organic solvent tends to be less likely to occur.

[0022] The average thickness of each B1 layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 1 μm or more, and particularly preferably 3 μm or more. On the other hand, the average thickness of each B1 layer is preferably 20 μm or less, more preferably 15 μm or less, even more preferably 10 μm or less, and particularly preferably 8 μm or less. When the average thickness of each B1 layer is 0.1 μm or more, it becomes relatively easy to mold the layer with a uniform thickness, and durability tends to be improved. In addition, sufficient flexibility is easily expressed. On the other hand, when the average thickness of each B1 layer is 20 μm or less, interlayer adhesion and gas barrier properties tend to be improved. In addition, when the average thickness of each B1 layer is 20 μm or less, recyclability tends to be improved. This is presumed to be because, when melt-kneading to recycle trim, etc., the metal salt contained in the A layer as necessary can be efficiently transferred to the entire polyurethane of the B1 layer. The term "recyclability" refers to a property that makes it easy to recycle, such as small fluctuations in the rotation torque of an extruder screw, when the trim of a multilayer structure or the like is melt-molded again for recycling.

[0023] The average thickness of each B2 layer is preferably 1 μm or more, more preferably 3 μm or more. On the other hand, the average thickness of each B2 layer is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less. When the average thickness of each B2 layer is 1 μm or more, durability tends to be improved. In addition, sufficient flexibility is easily exhibited. On the other hand, when the average thickness of each B2 layer is 30 μm or less, interlayer adhesion and gas barrier properties tend to be improved. In addition, when the average thickness of each B2 layer is 30 μm or less, recyclability tends to be improved. This is presumed to be because, when melt-kneading to recycle trim, etc., the metal salt contained in the A layer as necessary can efficiently migrate to the entire polyurethane of the B layer.

[0024] When the multilayer structure of the present invention includes a D layer, the average thickness of each D layer is preferably 300 μm or more, more preferably 350 μm or more, and even more preferably 400 μm or more. On the other hand, the average thickness of the D layer is preferably 800 μm or less, more preferably 750 μm or less, and even more preferably 700 μm or less. When the average thickness of the D layer is 300 μm or more, durability tends to be improved. In addition, sufficient flexibility is easily exhibited. Conversely, when the average thickness of the D layer is 800 μm or less, gas barrier properties after bending tend to be improved.

[0025] The total thickness of all layers of the A layer and all layers of the B layer may be, for example, 5 μm or more, but is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 30 μm or more. On the other hand, the total thickness of all layers of the A layer and all layers of the B layer is preferably 500 μm or less, more preferably 300 μm or less, and even more preferably 100 μm or less. When the total thickness of all layers of the A layer and all layers of the B layer is 10 μm or more, bending resistance, durability, gas barrier property, solvent resistance, etc. tend to be improved. On the other hand, when this total thickness is 500 μm or less, flexibility, moldability, etc. are improved, and bending resistance can be improved and manufacturing costs can be suppressed. In addition, recyclability may be improved by making the resin amount of the B layer appropriate. Here, the total thickness of all layers refers to the sum of the average thicknesses of each layer. In a multilayer structure consisting of only the A layer and the B layer, the thickness of the entire multilayer structure consisting of only the A layer and the B layer can be the total thickness. The average thickness of each layer is the average value of the thicknesses of the cross sections at 10 points selected arbitrarily.

[0026] The ratio of the average thickness per layer A to the average thickness per layer B (layer A / layer B) may be, for example, 0.05 or more, but is preferably 0.1 or more, more preferably 0.15 or more, and even more preferably 0.2 or 0.25 or more. The ratio is preferably 1 or less, more preferably 0.8 or less, and more preferably 0.6 or less. When the ratio (A / B) of the average thickness per layer A to the average thickness per layer B is 0.1 or more, cracking of the layer A due to stress during bending is reduced, and the deterioration of gas barrier properties tends to be suppressed, and the solvent resistance is also improved. When the ratio (A / B) is 1 or less, the stress during bending is alleviated by the layer B, and the cracking of the layer A is reduced, the deterioration of gas barrier properties is suppressed, and the solvent resistance tends to be improved. When the ratio of the average thickness per layer A to the average thickness per layer B is within the above range, the ratio of the resins of the layers A and B becomes favorable as a whole multilayer structure, and recyclability and the like tend to be improved.

[0027] The overall average thickness of the multilayer structure of the present invention is not particularly limited and can be appropriately set depending on the application, function, etc. For example, a relatively thin thickness can reduce the weight, and a relatively thick thickness can improve the gas barrier properties, etc. The lower limit of the overall average thickness of the multilayer structure of the present invention may be, for example, 5 μm, 10 μm, 15 μm, 30 μm, 100 μm, or 300 μm. On the other hand, the upper limit may be 3 mm, 1 mm, 500 μm, 300 μm, or 100 μm.

[0028] The interlayer adhesive strength between the A layer and the B layer of the multilayer structure of the present invention is preferably 300 g / 15 mm or more, more preferably 400 g / 15 mm or more, and even more preferably 500 g / 15 mm or more. The interlayer adhesive strength of the multilayer structure of the present invention may be 1500 g / 15 mm or less. If the interlayer adhesive strength is 300 g / 15 mm or more, delamination during bending or the like tends to be suppressed. As a means for increasing the interlayer adhesive strength of the multilayer structure of the present invention, there are methods such as adjusting the amount of thermoplastic resin (a2) added or the acid value, directly laminating the A layer and the B layer, or alternately laminating the A layer and the B layer. The interlayer adhesive strength of the multilayer structure of the present invention can be measured by the method described in the Examples.

[0029] The oxygen transmission rate (OTR) of the multilayer structure of the present invention measured at 20°C and 65% RH is 20 mL / (m 2 ·day·atm) or less is preferable, and 15mL / (m 2 ·day·atm) or less is more preferable, and 10mL / (m 2 ·day·atm) or less is more preferable. Also, the OTR is 0.2mL / (m 2 ·day·atm) or more. When the oxygen permeability of the multilayer structure of the present invention is within the above range, it can be suitably used as a material that requires gas barrier properties, durability, etc. In addition, the multilayer structure of the present invention has an OTR after bending of 60 mL / (m 2 ·day·atm) or less, and 20mL / (m 2 ·day·atm) or less. Also, the OTR after bending is 0.3mL / (m 2When the OTR after bending of the multilayer structure of the present invention is within the above range, it can be suitably used as a material that requires stretchability. The OTR and the OTR after bending of the present invention can be measured by the method described in the Examples.

[0030] The A layer is a layer containing EVOH (a1) and a thermoplastic resin (a2) having a functional group capable of reacting with EVOH (a1). In the A layer, the content of the thermoplastic resin (a2) is 0.1 to 30 parts by mass relative to 100 parts by mass of the total of EVOH (a1) and the thermoplastic resin (a2). When the A layer contains a specific amount of EVOH (a1) and the thermoplastic resin (a2), a multilayer structure having excellent gas barrier properties and solvent resistance can be obtained. The reason why the multilayer structure of the present invention has excellent solvent resistance is not clear, but it is presumed that, for example, the presence of a specific amount of the thermoplastic resin (a2) having a functional group capable of reacting with EVOH (a1) suppresses the swelling of the A layer when exposed to a solvent, and high adhesion between the A layer and the B layer is maintained.

[0031] The total content of EVOH (a1) and thermoplastic resin (a2) in layer A is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 99% by mass or more, and may be 100% by mass. The total content of EVOH (a1) and thermoplastic resin (a2) in the total resin components in layer A is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 99% by mass or more, and may be 100% by mass.

[0032] The swelling degree of the A layer when immersed in 1-propanol / water = 60 / 40 (mass ratio) at 40 ° C for 30 minutes is preferably 50 mass % or less, more preferably 40 mass % or less, and even more preferably 30 mass % or less. The swelling degree of the A layer may be 10 mass % or more. When the swelling degree of the A layer is within the above range, it approaches the swelling degree of the B layer, and even when exposed to an organic solvent such as immersion in an organic solvent, delamination of the multilayer structure tends to be suppressed. As a means for adjusting the swelling degree of the A layer to a low level, means such as increasing the amount of thermoplastic resin (a2) added or strengthening the kneading with EVOH (a1) can be mentioned. The swelling degree of the A layer can be measured by the method described in the examples.

[0033] EVOH(a1) EVOH (a1) is a polymer having ethylene units and vinyl alcohol units as main structural units. EVOH (a1) may contain one or more types of other structural units in addition to ethylene units and vinyl alcohol units. EVOH (a1) is usually obtained by polymerizing ethylene and vinyl ester and saponifying the resulting ethylene-vinyl ester copolymer.

[0034] The ethylene unit content of EVOH (a1) (i.e., the ratio of the number of ethylene units to the total number of monomer units in EVOH (a1)) is preferably 20 mol% or more, more preferably 25 mol% or more, and even more preferably 30 mol% or more. On the other hand, the ethylene unit content of EVOH (a1) is preferably 60 mol% or less, more preferably 55 mol% or less. When the ethylene unit content of EVOH (a1) is 20 mol% or more, the gas barrier property, melt moldability, solvent resistance, etc. under high humidity of the obtained multilayer structure are further improved. Conversely, when the ethylene unit content of EVOH (a1) is 60 mol% or less, the gas barrier property of the obtained multilayer structure is further improved.

[0035] The saponification degree of EVOH (a1) (i.e., the ratio of the number of vinyl alcohol units to the total number of vinyl alcohol units and vinyl ester units in EVOH (a1)) is preferably 80 mol% or more, more preferably 95 mol% or more, and particularly preferably 99 mol% or more. On the other hand, the saponification degree of EVOH (a1) is preferably 99.99 mol% or less. When the saponification degree of EVOH (a1) is 80 mol% or more, the melt moldability tends to be improved, and in addition, the gas barrier property of the obtained multilayer structure is further improved, and the coloring resistance and moisture resistance may also be improved. On the other hand, when the saponification degree of EVOH (a1) is 99.99 mol% or less, the gas barrier property and the like can be exhibited while suppressing an increase in the production cost of EVOH (a1). Such EVOH (a1) can be used alone, but an embodiment in which an EVOH having a saponification degree of more than 99 mol% is blended with another EVOH is also suitable.

[0036] EVOH (a1) preferably has at least one of a structural unit (I) represented by the following formula (I), a structural unit (II) represented by the following formula (II), and a structural unit (III) represented by the following formula (III). When EVOH (a1) has such a structural unit, the bending resistance, etc. of the obtained multilayer structure can be further improved.

[0037] [ka]

[0038] In the above formula (I), R 1 , R 2 and R 3 each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms, an alicyclic hydrocarbon group having 3 to 10 carbon atoms, an aromatic hydrocarbon group having 6 to 10 carbon atoms, or a hydroxyl group. 1 , R 2 and R 3One pair of these may be bonded to each other. In addition, some or all of the hydrogen atoms in the aliphatic hydrocarbon group having 1 to 10 carbon atoms, the alicyclic hydrocarbon group having 3 to 10 carbon atoms, and the aromatic hydrocarbon group having 6 to 10 carbon atoms may be substituted with a hydroxyl group, a carboxyl group, or a halogen atom.

[0039] In the above formula (II), R 4 , R 5 , R 6 and R 7 each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms, an alicyclic hydrocarbon group having 3 to 10 carbon atoms, an aromatic hydrocarbon group having 6 to 10 carbon atoms, or a hydroxyl group. 4 and R 5 , or R 6 and R 7 may be bonded to the aliphatic hydrocarbon group having 1 to 10 carbon atoms, the alicyclic hydrocarbon group having 3 to 10 carbon atoms, and the aromatic hydrocarbon group having 6 to 10 carbon atoms. Some or all of the hydrogen atoms in the aliphatic hydrocarbon group having 1 to 10 carbon atoms may be substituted with a hydroxyl group, an alkoxy group, a carboxy group, or a halogen atom.

[0040] In the above formula (III), R 8 , R 9 , R 10 and R 11 R each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms, an alicyclic hydrocarbon group having 3 to 10 carbon atoms, an aromatic hydrocarbon group having 6 to 10 carbon atoms, or a hydroxyl group. Some or all of the hydrogen atoms in the aliphatic hydrocarbon group having 1 to 10 carbon atoms, the alicyclic hydrocarbon group having 3 to 10 carbon atoms, and the aromatic hydrocarbon group having 6 to 10 carbon atoms may be substituted with a hydroxyl group, an alkoxy group, a carboxy group, or a halogen atom. 12 and R 13 each independently represents a hydrogen atom, a formyl group, or an alkanoyl group having 2 to 10 carbon atoms.

[0041] The content of the structural unit (I), (II) or (III) relative to the total structural units is preferably 0.5 mol% or more, more preferably 1 mol% or more, and even more preferably 1.5 mol% or more. Meanwhile, the content of the structural unit (I), (II) or (III) is preferably 30 mol% or less, more preferably 15 mol% or less, and even more preferably 10 mol% or less. By having the structural unit (I), (II) or (III) in the above range in EVOH (a1), the flexibility and processing properties of the material forming the A layer are improved, and as a result, the stretchability and thermoformability of the obtained multilayer structure can be improved.

[0042] In the structural unit (I), (II) or (III), examples of the aliphatic hydrocarbon group having 1 to 10 carbon atoms include an alkyl group, an alkenyl group, etc., examples of the alicyclic hydrocarbon group having 3 to 10 carbon atoms include a cycloalkyl group, a cycloalkenyl group, etc., and examples of the aromatic hydrocarbon group having 6 to 10 carbon atoms include a phenyl group, etc.

[0043] In the structural unit (I), the R 1 , R 2 and R 3 are preferably each independently a hydrogen atom, a methyl group, an ethyl group, a hydroxyl group, a hydroxymethyl group, or a hydroxyethyl group, and among these, are more preferably each independently a hydrogen atom, a methyl group, a hydroxyl group, or a hydroxymethyl group. 1 , R 2 and R 3 This can further improve the stretchability and thermoformability of the resulting multilayer structure.

[0044] The method for incorporating the structural unit (I) in EVOH (a1) is not particularly limited, and examples thereof include a method of copolymerizing a monomer derived from the structural unit (I) in the polymerization of ethylene and a vinyl ester. Monomers derived from this structural unit (I) include alkenes such as propylene, butylene, pentene, and hexene; 3-hydroxy-1-propene, 3-acyloxy-1-propene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-hydroxy-1-butene, 4-acyloxy-3-hydroxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-2-methyl-1-butene, 4-acyloxy-3-methyl-1-butene, 3,4-diacyloxy-2-methyl-1-butene, 4-hydroxy-1-pentene, 5-hydroxy-1-pentene, Examples of alkenes having a hydroxyl group or an ester group include 4,5-dihydroxy-1-pentene, 4-acyloxy-1-pentene, 5-acyloxy-1-pentene, 4,5-diacyloxy-1-pentene, 4-hydroxy-3-methyl-1-pentene, 5-hydroxy-3-methyl-1-pentene, 4,5-dihydroxy-3-methyl-1-pentene, 5,6-dihydroxy-1-hexene, 4-hydroxy-1-hexene, 5-hydroxy-1-hexene, 6-hydroxy-1-hexene, 4-acyloxy-1-hexene, 5-acyloxy-1-hexene, 6-acyloxy-1-hexene, and 5,6-diacyloxy-1-hexene. Among them, from the viewpoint of copolymerization reactivity and gas barrier properties of the resulting multilayer structure, propylene, 3-acetoxy-1-propene, 3-acetoxy-1-butene, 4-acetoxy-1-butene and 3,4-diacetoxy-1-butene are preferred. In the case of an alkene having an ester, it is derived into the above structural unit (I) during the saponification reaction.

[0045] In the structural unit (II), R 4 and R 5 Preferably, both are hydrogen atoms. 4 and R 5 are both hydrogen atoms, and the above R 6 and R 7It is more preferable that one of R is an aliphatic hydrocarbon group having 1 to 10 carbon atoms, and the other is a hydrogen atom. The aliphatic hydrocarbon group is preferably an alkyl group or an alkenyl group. From the viewpoint of placing particular importance on the gas barrier property of the resulting multilayer structure, R 6 and R 7 It is particularly preferred that one of the R 6 and R 7 One of them is (CH2) h It is particularly preferred that the other of the substituents represented by OH (wherein h is an integer of 1 to 8) is a hydrogen atom. h In the substituent represented by OH, h is preferably an integer of 1 to 4, more preferably 1 or 2, and particularly preferably 1.

[0046] The method for incorporating the structural unit (II) in EVOH (a1) is not particularly limited, but may be a method of incorporating the structural unit (II) by reacting a monofunctional epoxy compound with EVOH obtained by saponification reaction. As the monofunctional epoxy compound, the compounds represented by the following formulae (IV) to (X) are preferably used.

[0047] [ka]

[0048] In the above formulas (IV) to (X), R 14 , R 15 , R 16 , R 17 and R 18 each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms (such as an alkyl group or an alkenyl group), an alicyclic hydrocarbon group having 3 to 10 carbon atoms (such as a cycloalkyl group or a cycloalkenyl group), or an aliphatic hydrocarbon group having 6 to 10 carbon atoms (such as a phenyl group). In addition, i, j, k, p, and q each independently represent an integer of 1 to 8.

[0049] Examples of the monofunctional epoxy compound represented by the above formula (IV) include epoxyethane (ethylene oxide), epoxypropane, 1,2-epoxybutane, 2,3-epoxybutane, 3-methyl-1,2-epoxybutane, 1,2-epoxypentane, 3-methyl-1,2-epoxypentane, 1,2-epoxyhexane, 2,3-epoxyhexane, 3,4-epoxyhexane, 3-methyl-1,2-epoxyhexane, 3-methyl-1,2-epoxyheptane, 4-methyl-1,2-epoxyheptane, 1,2-epoxyoctane, 2,3-epoxyoctane, 1,2-epoxynonane, 2,3-epoxynonane, 1,2-epoxydecane, 1,2-epoxydodecane, epoxyethylbenzene, 1-phenyl-1,2-epoxypropane, 3-phenyl-1,2-epoxypropane, etc. Examples of the monofunctional epoxy compound represented by the above formula (V) include various alkyl glycidyl ethers, etc. Examples of the monofunctional epoxy compound represented by the above formula (VI) include various alkylene glycol monoglycidyl ethers. Examples of the monofunctional epoxy compound represented by the above formula (VII) include various alkenyl glycidyl ethers. Examples of the monofunctional epoxy compound represented by the above formula (VIII) include various epoxy alkanols such as glycidol. Examples of the monofunctional epoxy compound represented by the above formula (IX) include various epoxy cycloalkanes. Examples of the monofunctional epoxy compound represented by the above formula (X) include various epoxy cycloalkenes.

[0050] Among the monofunctional epoxy compounds, an epoxy compound having 2 to 8 carbon atoms is preferred. In particular, from the viewpoint of ease of handling of the compound and reactivity, the number of carbon atoms in the monofunctional epoxy compound is more preferably 2 to 6, and even more preferably 2 to 4. In addition, among the above formulas, the monofunctional epoxy compound is particularly preferably a compound represented by formula (IV) or (V). Specifically, from the viewpoint of reactivity with EVOH (a1) and the gas barrier properties of the resulting multilayer structure, 1,2-epoxybutane, 2,3-epoxybutane, epoxypropane, epoxyethane, and glycidol are preferred, and among them, epoxypropane and glycidol are particularly preferred.

[0051] In the structural unit (III), R 8 , R 9 , R 10 and R 11 is preferably a hydrogen atom or an aliphatic hydrocarbon group having 1 to 5 carbon atoms. Particularly preferred examples of the aliphatic hydrocarbon group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, and a pentyl group.

[0052] The method for incorporating the structural unit (III) in EVOH (a1) is not particularly limited, and the EVOH (a1) can be produced, for example, by the method described in JP-A-2014-034647.

[0053] <Thermoplastic resin (a2)> The thermoplastic resin (a2) is a thermoplastic resin having a functional group capable of reacting with EVOH (a1). The functional group is preferably a group that reacts with a hydroxyl group of EVOH (a1). Specific examples of the functional group include a carboxy group or a derivative thereof, a phosphoric acid group or a derivative thereof, an epoxy group, an amino group, and a halogen. Examples of derivatives of a carboxy group include a carboxylic anhydride group (-CO-O-CO-), a carboxylic acid chloride group (-COCl, -COBr, etc.), and the like. Among these, an acidic group such as a carboxy group, a phosphoric acid group, or a derivative thereof is preferred, and a carboxy group or a derivative thereof is more preferred. The acidic group may be present in the form of a salt.

[0054] As the thermoplastic resin (a2), a modified thermoplastic resin containing a carboxy group obtained by chemically bonding (for example, addition reaction, graft reaction, copolymerization, etc.) an ethylenically unsaturated carboxylic acid or its anhydride to a thermoplastic resin can be preferably used. As the thermoplastic resin into which a functional group (modified group) is introduced, an olefin-based polymer is preferably used. As the olefin-based polymer, polyolefins such as polyethylene, polypropylene, polybutene, etc., copolymers of olefins and other monomers (vinyl esters, unsaturated carboxylic acid esters, styrene, etc.) (for example, ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, SEBS (hydrogenated block copolymers of styrene and butadiene), etc.) are used. Among them, polyethylene, polypropylene, ethylene-vinyl acetate copolymers (vinyl acetate content of 5 to 55% by mass), and ethylene-ethyl acrylate copolymers (ethyl acrylate content of 8 to 35% by mass) are preferred, polyethylene, polypropylene, and ethylene-vinyl acetate copolymers are more preferred, and polyethylene and polypropylene are particularly preferred.

[0055] Examples of the ethylenically unsaturated carboxylic acid or its anhydride include an ethylenically unsaturated monocarboxylic acid or its ester, an ethylenically unsaturated dicarboxylic acid or its mono- or diester, or its anhydride, and among these, an ethylenically unsaturated dicarboxylic acid anhydride is preferred.Specific examples include maleic acid, fumaric acid, itaconic acid, maleic anhydride, itaconic anhydride, maleic acid monomethyl ester, maleic acid monoethyl ester, maleic acid diethyl ester, fumaric acid monomethyl ester, and the like, and maleic anhydride is particularly preferred.

[0056] Thus, the thermoplastic resin (a2) is preferably a modified olefin polymer, more preferably a modified polyethylene, modified polypropylene, modified ethylene-vinyl acetate copolymer, and modified ethylene-ethyl acrylate copolymer. Also, modified polyolefin is preferable, and modified polyethylene and modified polypropylene are more preferable. These modified olefin polymers, modified polyolefins, modified polyethylene, modified polypropylene, modified ethylene-vinyl acetate copolymer, and modified ethylene-ethyl acrylate copolymer are each preferably an acid-modified product, and more preferably a carboxylic acid-modified product. These thermoplastic resins (a2) may be used alone or in a mixture of two or more kinds.

[0057] It may be preferable that the thermoplastic resin (a2) is a resin having a 100% modulus of 6 MPa or more at −30° C. If the 100% modulus of the thermoplastic resin (a2) at −30° C. is less than 6 MPa, it may affect the solvent resistance, etc.

[0058] The amount of functional group (modified group) added or grafted (degree of modification) to the thermoplastic resin is 0.0001 to 15% by mass, preferably 0.001 to 10% by mass, based on the unmodified thermoplastic resin. The addition reaction or graft reaction of the functional group (modified group) to the thermoplastic resin can be carried out, for example, by radical polymerization in the presence of a solvent (such as xylene) and a catalyst (such as peroxide).

[0059] The lower limit of the melt flow rate (MFR) of the thermoplastic resin (a2) measured at 190°C and a load of 2160g is preferably 0.2g / 10min, more preferably 0.5g / 10min, and even more preferably 1.5g / 10min. On the other hand, the upper limit of this MFR is preferably 1100g / 10min, more preferably 900g / 10min, and even more preferably 800g / 10min. By setting the MFR of the thermoplastic resin (a2) within the above range, the dispersibility becomes good, and the gas barrier property, interlayer adhesion, recyclability, solvent resistance, etc. tend to be better.

[0060] The acid value of the thermoplastic resin (a2) is preferably 0.5 mgKOH / g or more, more preferably 5 mgKOH / g or more, and even more preferably 15 mgKOH / g or more. The acid value of the thermoplastic resin (a2) is preferably 100 mgKOH / g or less, more preferably 50 mgKOH / g or less, and even more preferably 40 mgKOH / g or less. When the acid value of the thermoplastic resin (a2) is 0.5 mgKOH / g or more, the swelling degree of the A layer decreases, and the solvent resistance (interlayer peel resistance) tends to improve. When the acid value of the thermoplastic resin (a2) is 100 mgKOH / g or less, the dispersibility of the thermoplastic resin improves, and the interlayer adhesive strength and recyclability tend to improve. The acid value of the thermoplastic resin (a2) can be measured based on JIS K 0070 (1992).

[0061] The content of the thermoplastic resin (a2) in the A layer is 0.1 parts by mass or more, preferably 1 part by mass or more, more preferably 3 parts by mass or more, based on 100 parts by mass of the total of the EVOH (a1) and the thermoplastic resin (a2). The content of the thermoplastic resin (a2) is 30 parts by mass or less, preferably 20 parts by mass or less, more preferably 15 parts by mass or less, based on 100 parts by mass of the total of the EVOH (a1) and the thermoplastic resin (a2). If the content of the thermoplastic resin (a2) is less than 0.1 parts by mass, the solvent resistance is low, and the interlayer peel resistance when exposed to an organic solvent tends to be insufficient. If the content of the thermoplastic resin (a2) exceeds 30 parts by mass, the appearance and gas barrier properties of the multilayer structure of the present invention are deteriorated, and the rotation torque fluctuation of the extruder screw tends to increase when the trim of the multilayer structure of the present invention is melt-molded again for recycling.

[0062] It is preferable that layer A forms a phase-separated structure having a sea phase and an island phase, and it is preferable that the sea phase contains EVOH (a1) and the island phase contains a thermoplastic resin (a2).

[0063] When the A layer forms a phase-separated structure having the above-mentioned sea-island structure, the dispersed particle size of the island phase is preferably 1 μm or less, more preferably less than 0.5 μm, and even more preferably less than 0.4 μm or less than 0.3 μm. The dispersed particle size of the island phase may be 0.1 μm or more. For example, a method of adjusting the dispersed particle size may be used, such as a method of adjusting the acid value of the thermoplastic resin (a2). In addition, it is preferable that the island phase further comprises a phase containing EVOH (a1), and it is more preferable that the EVOH (a1) is dispersed in a scattered dot shape. When the island phase further comprises a phase containing EVOH (a1), the dispersed particle size is preferably 0.5 μm or less, more preferably less than 0.3 μm, and may be 0.005 μm or more. For example, a method of adjusting the film-forming conditions when forming a multilayer structure may be used, such as a method of adjusting the film-forming conditions when forming a multilayer structure. When a phase containing EVOH (a1) is formed inside the island phase containing the thermoplastic resin (a2), the recyclability of the A layer can be improved.

[0064] <Higher fatty acid metal salts (a3)> It is preferable that the A layer contains a higher fatty acid metal salt (a3). The content of the higher fatty acid metal salt (a3) ​​in the A layer is preferably 10 ppm or more and 300 ppm or less in terms of metal atoms. Here, in this specification, "higher fatty acid" means a fatty acid having 10 or more carbon atoms. In addition, in this specification, "ppm" is a content based on mass. It is preferable that the A layer contains the higher fatty acid metal salt (a3), because it can reduce the deterioration of color and the amount of deteriorated resin adhering to the screw in the melt molding machine when the trim or the like is subjected to melt molding again for recycling. In addition, if the amount of deteriorated resin adhering to the screw in the melt molding machine is small, the rotation torque fluctuation is small, and molding can be performed stably for a long period of time.

[0065] The metal atom constituting the higher fatty acid metal salt (a3) ​​may be a single metal species or may be composed of a plurality of metal species. The metal atom is preferably a divalent metal. Among them, it is preferable to include at least one selected from the group consisting of magnesium, manganese, tin, cobalt, zinc, cadmium, lead and titanium, and more preferably to include at least one selected from the group consisting of magnesium, cobalt, tin and titanium. Among them, it is preferable to include magnesium or cobalt. By including the above metal atom, the A layer and the B layer tend to show higher adhesion. Although the reason for the high adhesion is not clear, it is considered that the compound containing the above metal atom tends to promote the transesterification reaction, and such a reaction may contribute to the improvement of adhesion.

[0066] The lower limit of the carbon number of the higher fatty acid constituting the higher fatty acid metal salt (a3) ​​is preferably 12, more preferably 13, and further preferably 14, 15, 16, 17, and 18. The upper limit of the carbon number is, for example, 30, and may be 24, 22, or 20. Examples of the higher fatty acid constituting the higher fatty acid metal salt (a3) ​​include stearic acid, ricinoleic acid, myristic acid, and lauric acid, and among these, stearic acid is preferred. By including the above-mentioned higher fatty acid, deterioration of the hue tends to be suppressed, and therefore it is preferred.

[0067] As the higher fatty acid metal salt (a3), for example, magnesium stearate, cobalt stearate, etc. are preferably used.

[0068] The content of the higher fatty acid metal salt (a3) ​​is preferably 10 ppm or more in terms of metal atoms, more preferably 20 ppm or more, and even more preferably 30 ppm or more. The content of the higher fatty acid metal salt (a3) ​​is preferably 300 ppm or less in terms of metal atoms, more preferably 200 ppm or less, and even more preferably 100 ppm or less. When the content of the higher fatty acid metal salt (a3) ​​is 10 ppm or more in terms of metal atoms, the interlayer adhesive strength and recyclability tend to improve. When the content of the higher fatty acid metal salt (a3) ​​is 300 ppm or less in terms of metal atoms, the deterioration of the hue can be suppressed, and the recyclability also tends to increase.

[0069] One or more additives such as phosphoric acid compounds, carboxylic acids, boron compounds, metal salts other than higher fatty acid metal salts (a3), etc. can be added to layer A within a range that does not impair the effects of the present invention. By adding these additives to EVOH (a1) constituting layer A, etc., various properties of the resulting multilayer structure can be improved.

[0070] As the phosphoric acid compound, for example, various acids such as phosphoric acid and phosphorous acid and salts thereof can be used. The phosphate may be in the form of any of primary phosphate, secondary phosphate and tertiary phosphate. The cationic species of the phosphate is not particularly limited, but the cationic species is preferably an alkali metal or an alkaline earth metal. Among them, it is preferable to add the phosphoric acid compound as sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate or dipotassium hydrogen phosphate. When the A layer contains a phosphoric acid compound, the content thereof is preferably 1 to 500 ppm in terms of phosphate radical. When the A layer contains a phosphoric acid compound, the long-run property when the A layer is formed for a long time tends to be improved.

[0071] The carboxylic acids contained in layer A may be carboxylic acids, carboxylate ions, or carboxylic acid derivatives. The carboxylic acids may be monocarboxylic acids, polycarboxylic acids having two or more carboxyl groups in the molecule, or combinations thereof. The polycarboxylic acids do not include polymers. The polycarboxylic acid ions are those in which at least one hydrogen ion has been eliminated from the carboxyl group of the polycarboxylic acid. The carboxyl group of the carboxylic acid may be esterified, and the carboxylate ions may form a salt with a metal. The number of carbon atoms of the carboxylic acids is preferably less than 10.

[0072] The monocarboxylic acid is not particularly limited, and examples thereof include formic acid, acetic acid, propionic acid, butyric acid, caproic acid, capric acid, acrylic acid, methacrylic acid, benzoic acid, and 2-naphthoic acid. These carboxylic acids may have a hydroxyl group or a halogen atom. In addition, examples of the carboxylate ion include those in which a hydrogen ion has been eliminated from the carboxyl group of each of the above carboxylic acids. The pKa of this monocarboxylic acid (including monocarboxylic acids that give monocarboxylate ions) is preferably 3.5 or more, more preferably 4 or more, from the viewpoint of the pH adjusting ability and melt moldability of the composition. Examples of such monocarboxylic acids include formic acid (pKa=3.68), acetic acid (pKa=4.74), propionic acid (pKa=4.85), and butyric acid (pKa=4.80), and acetic acid is preferred from the viewpoint of ease of handling.

[0073] In addition, the polyvalent carboxylic acid is not particularly limited as long as it has two or more carboxy groups in the molecule, and examples thereof include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, maleic acid, fumaric acid, glutaric acid, adipic acid, and pimelic acid; aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid; tricarboxylic acids such as aconitic acid; carboxylic acids having four or more carboxy groups such as 1,2,3,4-butanetetracarboxylic acid and ethylenediaminetetraacetic acid; hydroxycarboxylic acids such as tartaric acid, citric acid, isocitric acid, malic acid, mucic acid, tartronic acid, and citramalic acid; ketocarboxylic acids such as oxaloacetic acid, mesoxalic acid, 2-ketoglutaric acid, and 3-ketoglutaric acid; and amino acids such as glutamic acid, aspartic acid, and 2-aminoadipic acid. In addition, examples of the polyvalent carboxylate ion include these anions. Among these, succinic acid, malic acid, tartaric acid, and citric acid are particularly preferred because they are easily available.

[0074] When layer A contains a carboxylic acid, the content thereof is preferably 0.5 μmol / g to 20 μmol / g calculated as a carboxylic acid radical from the viewpoint of coloration resistance during melt molding.

[0075] Examples of boron compounds include boric acids, boric acid esters, borate salts, boron hydrides, etc. Specifically, examples of boric acids include orthoboric acid (hereinafter also simply referred to as "boric acid"), metaboric acid, tetraboric acid, etc., examples of borate esters include triethyl borate, trimethyl borate, etc., and examples of borates include alkali metal salts, alkaline earth metal salts, borax, etc. of the various boric acids mentioned above. Among these compounds, orthoboric acid is preferred.

[0076] When the layer A contains a boron compound, the content thereof is preferably 20 to 2000 ppm in terms of elemental boron, from the viewpoint of improving the film formation stability of the layer A.

[0077] Examples of metal salts other than the higher fatty acid metal salt (a3) ​​include lower fatty acid metal salts having less than 10 carbon atoms, metal salts of organic acids other than fatty acids, and metal salts of inorganic acids. Metals used in such metal salts are preferably alkali metals or alkaline earth metals. Examples of alkali metals include lithium, sodium, potassium, and the like, and examples of alkali metal salts include lower aliphatic carboxylates, aromatic carboxylates, phosphates, and metal complexes of alkali metals. Examples include sodium acetate, potassium acetate, sodium phosphate, potassium phosphate, and sodium salt of ethylenediaminetetraacetic acid, and among these, sodium acetate, potassium acetate, sodium phosphate, and potassium phosphate are preferred. When layer A contains an alkali metal salt other than the higher fatty acid metal salt (a3), the content is preferably 20 to 1000 ppm in terms of metal atom from the viewpoint of enhancing interlayer adhesion. Examples of alkaline earth metals include beryllium, magnesium, calcium, strontium, barium, and the like, and magnesium or calcium is more preferred from the viewpoint of industrial availability. Examples of the alkaline earth metal salt include lower aliphatic carboxylates, aromatic carboxylates, phosphates, and metal complexes of alkaline earth metals. Examples include magnesium acetate, calcium acetate, magnesium phosphate, and calcium phosphate, and among these, magnesium acetate and calcium acetate are preferred. When Layer A contains an alkaline earth metal salt other than the higher fatty acid metal salt (a3), the content is preferably 20 to 1000 ppm in terms of metal atom. By containing the alkaline earth metal salt in the above range, Layer A and Layer B tend to show higher adhesion. In addition, deterioration of EVOH during repeated reuse of the multilayer structure is suppressed, and defects such as gels and bumps are reduced, improving the appearance of the molded product.

[0078] Layer A may contain other resins other than EVOH (a1) and thermoplastic resin (a2) within the range that does not impair the effects of the present invention. Examples of such other resins include polyethylene, polypropylene, ethylene-propylene copolymers, ethylene or propylene copolymers (copolymers of ethylene or propylene with at least one of the following monomers: α-olefins such as 1-butene, isobutene, 4-methyl-1-pentene, 1-hexene, 1-octene, etc.; vinylpyrrolidones, etc.), polyolefins such as poly4-methyl-1-pentene and poly1-butene; polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyvinylidene chloride, polyvinyl chloride, polystyrene, polycarbonate, and polyacrylate.

[0079] In addition to the above-mentioned other resins, Layer A may contain various components such as heat stabilizers, ultraviolet absorbers, antioxidants, colorants, fillers, plasticizers, photoinitiators, deodorizers, antistatic agents, lubricants, desiccants, bulking agents, pigments, dyes, processing aids, flame retardants, and antifogging agents.

[0080] The B layer is a polyurethane layer containing TPU (b). The multilayer structure of the present invention can exhibit good stretchability, bending resistance, thermoformability, etc. by having the B layer containing TPU (b). The swelling degree of the B layer when immersed in 1-propanol / water = 60 / 40 mass% at 40 ° C. for 30 minutes is preferably 30 mass % or less, more preferably 25 mass % or less, and even more preferably 20 mass % or less. The swelling degree of the B layer may be 5 mass % or more. When the swelling degree of the B layer is within the above range, it approaches the swelling degree of the A layer, and even when immersed in an organic solvent, it tends to be possible to suppress delamination of the multilayer structure. The swelling degree of the B layer can be measured by the method described in the examples. Moreover, the difference in swelling degree between the A layer and the B layer is preferably 35 mass % or less, more preferably 30 mass % or less, more preferably 20 mass % or less, and particularly preferably 15 mass % or less. When the swelling degree difference is within the above range, it tends to be possible to further suppress delamination of the multilayer structure when immersed in an organic solvent.

[0081] It is preferable that the B layer contains TPU (b) since it can improve stretchability, thermoformability, etc. In addition, in the multilayer structure of the present invention, good flex resistance, etc. can be achieved due to the high interlayer adhesion between the B layer and the A layer.

[0082] The content of TPU (b) in layer B is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, still more preferably 95% by mass or more, even more preferably 99% by mass or more, and may be 100% by mass.

[0083] TPU(b) is composed of a polymer polyol, an organic polyisocyanate, a chain extender, etc. Typically, TPU(b) is a linear multiblock copolymer of (1) a hard segment obtained by the reaction of a short-chain glycol (low molecular weight polyol) with an isocyanate, and (2) a soft segment obtained by the reaction of a long-chain glycol (polymer polyol) with an isocyanate.

[0084] The polymer polyol is a substance having a plurality of hydroxyl groups, and is obtained by polycondensation, addition polymerization (e.g., ring-opening polymerization), polyaddition, etc. Examples of the polymer polyol include polyester polyol, polyether polyol, polycarbonate polyol, and co-condensates thereof (e.g., polyester-ether-polyol). These polymer polyols may be used alone or in combination of two or more. However, polyester polyol and polycarbonate polyol are preferred, and polyester polyol is particularly preferred.

[0085] The polyester polyol can be produced, for example, by condensing an ester-forming derivative such as a dicarboxylic acid, an ester thereof or an anhydride thereof with a low-molecular-weight polyol through a direct esterification reaction or an ester exchange reaction, or by ring-opening polymerization of a lactone, according to a conventional method.

[0086] Examples of the polyether polyol include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, poly(methyltetramethylene) glycol, etc. These polyether polyols may be used alone or in combination of two or more. Among them, polytetramethylene glycol is preferred.

[0087] As the polycarbonate polyol, for example, one obtained by reacting an aliphatic diol having 2 to 12 carbon atoms, such as 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, or 1,10-decanediol, or a mixture thereof with diphenyl carbonate or phosgene to cause condensation polymerization is suitably used.

[0088] The lower limit of the number average molecular weight of the polymer polyol is preferably 500, more preferably 600, and even more preferably 700. On the other hand, the upper limit of the number average molecular weight of the polymer polyol is preferably 8,000, more preferably 5,000, and even more preferably 3,000. By setting the number average molecular weight of the polymer polyol to the above lower limit or more, the compatibility with the organic polyisocyanate becomes moderate, and the elasticity of the obtained TPU is improved, so that the mechanical properties such as stretchability and thermoformability of the obtained multilayer structure tend to be improved. On the other hand, by setting the number average molecular weight of the polymer polyol to the above upper limit or less, the compatibility with the organic polyisocyanate is improved, and mixing during the polymerization process is facilitated, and as a result, the generation of gel-like lumps is suppressed, and a stable TPU may be easily obtained. The number average molecular weight of the polymer polyol is a number average molecular weight measured in accordance with JIS K 1577 and calculated based on the hydroxyl value.

[0089] The organic polyisocyanate is not particularly limited, and known organic diisocyanates generally used in the production of TPU are used, such as aromatic diisocyanates such as 4,4'-diphenylmethane diisocyanate, tolylene diisocyanate, phenylene diisocyanate, xylylene diisocyanate, 1,5-naphthylene diisocyanate, 3,3'-dichloro-4,4'-diphenylmethane diisocyanate, and toluylene diisocyanate; and aliphatic diisocyanates (including alicyclic diisocyanates) such as hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and hydrogenated xylylene diisocyanate. Among them, 4,4'-diphenylmethane diisocyanate is preferred in that it can improve the strength and flex resistance of the resulting multilayer structure. These organic diisocyanates may be used alone or in combination of two or more.

[0090] As the chain extender, a chain extender generally used in the production of TPU is used, and a low molecular weight compound having two or more active hydrogen atoms in the molecule capable of reacting with an isocyanate group and a molecular weight of 300 or less is preferably used. Examples of the chain extender include ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,4-bis(β-hydroxyethoxy)benzene, and 1,4-cyclohexanediol. Among these, aliphatic diols having 2 to 10 carbon atoms are preferred, and 1,4-butanediol is particularly preferred, in that the stretchability and thermoformability of the resulting multilayer structure are further improved. These chain extenders may be used alone or in combination of two or more.

[0091] The TPU (b) can be produced by using the above-mentioned high molecular weight polyol, organic polyisocyanate and chain extender, utilizing a known urethane reaction technique, and can be produced by either a prepolymer method or a one-shot method. Among these, melt polymerization in the substantial absence of a solvent is preferred, and continuous melt polymerization using a multi-screw extruder is particularly preferred.

[0092] The B layer may be composed of only TPU(b) or may contain other resins other than TPU(b). The B layer may further contain other components such as a heat stabilizer, an ultraviolet absorber, an antioxidant, a colorant, an antistatic agent, a lubricant, and a filler in addition to the other resins. The preferred embodiments of the B1 layer and the B2 layer are the same as those of the B layer except for the average thickness.

[0093] <D layer> The D layer is a protective layer that is directly laminated on the B2 layer, and contains TPU(x). When the multilayer structure of the present invention contains the D layer, durability and flexibility are increased, and the gas barrier property after bending tends to be maintained well. A preferred embodiment of the TPU(x) is the same as the preferred embodiment of the TPU(b) that is a component of the B layer, except for the content. The content of the TPU(x) in the D layer is preferably 70% by mass or more and 99% by mass or less, more preferably 80% by mass or more and 98% by mass or less.

[0094] The D layer preferably contains EVOH(y). When the D layer contains EVOH(y), the gas barrier property after bending tends to be maintained well. A suitable embodiment of EVOH(y) is the same as the suitable embodiment of EVOH(a1) which is a component of the A layer, except for the content. The content of EVOH(y) in the D layer is preferably 1% by mass or more and 30% by mass or less, more preferably 2% by mass or more and 20% by mass or less.

[0095] It is preferable that the D layer contains a thermoplastic resin (z). When the D layer contains the thermoplastic resin (z), the solvent resistance and durability tend to be good. A suitable embodiment of the thermoplastic resin (z) is the same as the suitable embodiment of the thermoplastic resin (a2) which is a component of the A layer, except for the content. The content of the thermoplastic resin (z) in the D layer is preferably 0.001% by mass or more and 10% by mass or less, more preferably 0.01% by mass or more and 7% by mass or less, and even more preferably 0.03% by mass or more and 4% by mass or less.

[0096] From the viewpoint of cost reduction, it is preferable that the layer D is a layer made from recycled materials such as trims and out-of-spec products of the multilayer structure of the present invention.

[0097] Methods for using recycled trims, out-of-spec products, etc. of the multilayer structure of the present invention include a method of crushing the trims or out-of-spec products, feeding them into an extruder and forming a film, or a method of melt-kneading them in an extruder to prepare pellets, and then feeding the pellets again into the extruder to form a film. In order to control the thickness of the D layer or to dilute with new TPU, a method of melt-kneading them to prepare pellets, and then feeding the pellets again into the extruder to form a film is preferred.

[0098] The content ratio x / y of TPU(x) and EVOH(y) in the D layer is preferably 70 / 30 or more, more preferably 75 / 25 or more, and even more preferably 80 / 20 or more. On the other hand, the content ratio x / y is preferably 100 / 0 or less, more preferably 99 / 1 or less, and even more preferably 98 / 2 or less. When the content ratio x / y is within the above range, sufficient flexibility is exhibited, and the gas barrier property after bending tends to be maintained well.

[0099] The ratio of the total amount of TPU (x) and EVOH (y) constituting the D layer to the D layer is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more. When the total amount of TPU (x) and EVOH (y) constituting the D layer is 80% by mass or more of the ratio of the D layer to the D layer, the gas barrier property after bending can be maintained and sufficient flexibility is easily expressed. The ratio of the total amount of TPU (x) and EVOH (y) constituting the D layer to the D layer may be 99% by mass or more.

[0100] <Uses, etc.> The multilayer structure of the present invention is excellent in interlayer adhesion, gas barrier properties, appearance, flex resistance, solvent resistance, etc., and can therefore be used for food packaging materials, medical container packaging materials, other container packaging materials, industrial sheet materials, etc., building sheet materials, agricultural sheet materials, geomembranes, radon barrier films, other sheet materials, various other pipes, etc. In particular, the multilayer structure of the present invention is suitably used as a gas barrier film laminated on membranous rubber products such as tire inner liners, shoe sole air cushion materials, accumulator inner bags, air-filled balls, air springs, etc.

[0101] <Method for producing multilayer structure> The method for producing the multilayer structure of the present invention is not particularly limited as long as the method is capable of satisfactorily laminating and adhering the A layer and the B layer, and any known method such as coextrusion, lamination, coating, bonding, adhesion, etc. can be used.

[0102] The multilayer structure of the present invention can be preferably produced by a production method including a step of co-extruding a resin forming layer A and a resin forming layer B. Such a production method has high productivity, provides excellent interlayer adhesion between layers A and B, and is also excellent in recyclability.

[0103] In the multilayer coextrusion method, the resins forming the A layer and the resins forming the B layer are heated and melted, fed to an extrusion die through respective flow paths from different extruders or pumps, and extruded in multiple layers from the extrusion die and then laminated and bonded to form the multilayer structure of the present invention. For example, a multi-manifold die, a field block, a static mixer, etc. can be used as the extrusion die.

[0104] The viscosity of each resin forming the A layer and the B layer is preferably in the following melt viscosity ratio: That is, the melt viscosity (η A ) and the melt viscosity of the resin that forms the B layer (η B ) and the ratio (η B / η A The lower limit of the melt viscosity ratio (η B / η A The upper limit of the melt viscosity ratio (η B / η A ) in the above range, the appearance of the multilayer structure of the present invention can be improved when it is molded by a multilayer coextrusion method, and the adhesion between layer A and layer B can be improved, thereby improving the durability of the multilayer structure of the present invention.

[0105] The multilayer structure of the present invention can be produced in the same manner as described above even when it includes layers other than layers A and B, such as layer D. That is, each layer may be laminated by a known method such as coextrusion, lamination, coating, bonding, adhesion, etc., and among these, production by coextrusion is preferred.

[0106] The method for producing a multilayer structure of the present invention may include a step of irradiating the structure (multilayer structure) obtained by coextrusion with an electron beam. The electron beam irradiation causes a crosslinking reaction between layers, thereby increasing the interlayer adhesive strength of the obtained multilayer structure. As the electron beam source, various electron beam accelerators such as Cockcroft-Walton type, Van de Graft type, resonant transformer type, insulating core transformer type, dynamitron type, and high frequency type can be used.

[0107] <Molded body> A molded article according to one embodiment of the present invention includes the multilayer structure of the present invention. In the molded article of the present invention, at least one of the A layer and the B layer preferably contains a colorant. Examples of the molded article include containers, pipes, sheets, bags, and gas-filled cushioning materials, and gas-filled cushioning materials are preferred. The gas-filled cushioning material is formed by molding the multilayer structure of the present invention into a bag of a predetermined shape and filling it with gas. The gas-filled cushioning material is suitably used, for example, as a cushioning material for footwear (sole air cushioning material), etc.

[0108] The molded article of the present invention may be composed of only the multilayer structure of the present invention, or may further comprise a component other than the multilayer structure of the present invention. For example, the molded article may be obtained by laminating another resin layer or the like on the multilayer structure of the present invention and molding such a laminate into a predetermined shape.

[0109] The colorant contained in at least one of the A layer and the B layer of the multilayer structure constituting the molded product of the present invention may be either a pigment or a dye, and may be a white or black colorant. When the molded product of the present invention contains a colorant in at least one of the A layer and the B layer, the product has excellent design properties. The colorant may be contained only in a part of the A layer or the B layer. That is, the product may have a figure, a letter, or the like applied thereto by the colorant. On the other hand, the colorant may be contained in the entirety of at least one of the A layer and the B layer, and the entire multilayer structure may be colored in a predetermined color.

[0110] The molded article of the present invention uses the multilayer structure of the present invention, which has good gas barrier properties and flex resistance, and therefore, when it is used as a cushioning material filled with gas, the cushioning properties are maintained for a long period of time. In addition, since the multilayer structure of the present invention has excellent solvent resistance, the molded article of the present invention can be used in applications where it comes into contact with solvents, and even if it is obtained through a process where it comes into contact with a solvent, it still exhibits good performance.

[0111] <Method for producing molded body> The method for producing the molded article of the present invention is not particularly limited, but preferably includes a step (A) of contacting the multilayer structure with a treatment liquid containing an organic solvent. The treatment liquid preferably contains a colorant. The method for producing the molded article of the present invention may further include a step (B) of molding the multilayer structure. The order of the steps (A) and (B) is not particularly limited, but it is preferable to perform the steps (A) and (B) in that order.

[0112] According to the method for producing a molded article of the present invention, in step (A), a treatment liquid containing a colorant and an organic solvent is brought into contact with the multilayer structure, thereby impregnating at least one of layer A and layer B of the multilayer structure with the colorant, thereby coloring the multilayer structure. The contact of the treatment liquid with the multilayer structure can be carried out by immersing the multilayer structure in the treatment liquid, applying the treatment liquid, printing the treatment liquid, or the like.

[0113] The organic solvent contained in the treatment liquid is not particularly limited, and may be any liquid capable of sufficiently dissolving or dispersing the colorant. Examples of the organic solvent include alcohols such as methanol and ethanol, esters such as ethyl acetate and butyl acetate, ethers such as diethyl ether and ethylene glycol monobutyl ether, ketones such as acetone and cyclohexanone, and aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene. The treatment liquid may further contain other components such as water and a surfactant.

[0114] In the manufacturing method of the present invention, the multilayer structure is colored using a treatment liquid containing an organic solvent, and since the multilayer structure has excellent solvent resistance, high interlayer adhesion is maintained even after the coloring treatment. That is, even though the multilayer structure is exposed to an organic solvent during the manufacturing process, a molded product having excellent interlayer peel resistance can be obtained. In addition, for example, an uncolored multilayer structure can be colored in various variations using multiple types of treatment liquids, so that the productivity is excellent.

[0115] In another embodiment, in the method for producing a molded article of the present invention, the treatment liquid used in step (A) may not contain a colorant. For example, in step (A), a treatment liquid containing an adhesive and an organic solvent may be brought into contact with the multilayer structure to bond the multilayer structure to other components. Even when an organic solvent-based adhesive is used, the multilayer structure of the present invention has excellent solvent resistance, so that interlayer peeling is unlikely to occur, and good adhesion and molding can be performed. EXAMPLES

[0116] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0117] <Materials used> (EVOH(a1)) EVOH-1: "EVAL (registered trademark) E105B" (manufactured by Kuraray Co., Ltd., ethylene-vinyl alcohol copolymer, ethylene unit content 44 mol%) EVOH-2: "EVAL (registered trademark) F101B" (manufactured by Kuraray Co., Ltd., ethylene-vinyl alcohol copolymer, ethylene unit content 32 mol%) EVOH-3: "EVAL (registered trademark) L171B" (manufactured by Kuraray Co., Ltd., ethylene-vinyl alcohol copolymer, ethylene unit content 27 mol%) EVOH-4: "EVAL (registered trademark) G156B" (manufactured by Kuraray Co., Ltd., ethylene-vinyl alcohol copolymer, ethylene unit content 48 mol%) (thermoplastic resin (a2)) a2-1: "Scona (registered trademark) TPPP2112GA" (manufactured by BYK Japan Co., Ltd., maleic anhydride modified polypropylene (PP), acid value 21.8 mg KOH / g) a2-2: "Modic (registered trademark) P908" (manufactured by Mitsubishi Chemical Corporation, maleic anhydride modified PP, acid value 16.9 mg KOH / g) a2-3: "PRIEX (registered trademark) 25097" (Addcomp, maleic anhydride modified PP, acid value 12.1 mg KOH / g) a2-4: "Admer (registered trademark) QE840" (manufactured by Mitsui Chemicals, Inc., maleic anhydride modified PP, acid value 1.8 mgKOH / g) a2-5: "Rikeaid MG440P" (manufactured by Riken Vitamin Co., Ltd., maleic anhydride modified PP, acid value 49.6mgKOH / g) a2-6: "UMEX 1010" (Sanyo Chemical Industries, Ltd., maleic anhydride modified PP, acid value 81.1 mgKOH / g) a2-7: "LOTADER (registered trademark) 3210" (Tokyo Materials Co., Ltd., maleic anhydride modified ethylene-ethyl acrylate copolymer, acid value 17.4 mg KOH / g) a2-8: "ADMER (registered trademark) PF508" (maleic anhydride modified PP + maleic anhydride modified PE (polyethylene), manufactured by Mitsui Chemicals, Inc., acid value 6.7 mg KOH / g) a2-9: "Tuftec (registered trademark) M1943" (manufactured by Asahi Kasei Corporation, maleic anhydride modified SEBS, acid value 10.0 mg KOH / g) (TPU(b)) TPU-1: "Estane (registered trademark) 2103-90AE" (thermoplastic polyurethane manufactured by Lubrizol) (Higher fatty acid metal salts (a3)) StMg: Magnesium stearate, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0118] <Evaluation method> (1) Swelling degree The resin compositions constituting layer A or layer B obtained in the examples and comparative examples were subjected to monolayer film formation under the following conditions using a 20 mm extruder "D2020" (D (mm) = 20, L / D = 20, compression ratio = 2.0, screw: full flight) manufactured by Toyo Seiki Seisakusho Co., Ltd. to obtain a monolayer film. Extrusion temperature: Resin feed port / Cylinder inlet / Adapter / Die =180 / 200 / 200 / 200℃ Screw rotation speed: 40 rpm Discharge amount: 1.3kg / hr Take-up roll temperature: 80℃ Take-off roll speed: 1.1m / min. Film thickness: 60μm The obtained film was cut to 10 cm x 24 cm, and the mass was measured (W0). The cut film was immersed in 1-propanol / water = 60 / 40 (mass ratio) heated to 40 ° C for 30 minutes, the solvent on the film surface was wiped off with Kimtowel, and the mass was measured (W1). The swelling degree (S) was calculated from the following formula. S[mass%]={(W1-W0) / W0}×100

[0119] (2) Solvent resistance (resistance to delamination after immersion in organic solvent) The delamination resistance of the multilayer structures obtained in the Examples and Comparative Examples was evaluated as follows. The obtained multilayer structures were cut into 3 cm x 3 cm pieces, and the cut films were immersed in 1-propanol / water = 60 / 40 (mass ratio) heated to 40°C for 30 minutes, after which the solvent on the film surface was wiped off with a Kimtowel and allowed to cool for 2 hours. The presence or absence of delamination from the film edge to the film center, and if present, the length of delamination were measured, and the delamination resistance was evaluated based on the following evaluation criteria. Judgment criteria A: No delamination B: Less than 1 mm C: 1mm or more and less than 5mm D: 5mm or more

[0120] (3) Interlayer adhesion between layers A and B The interlayer adhesive strength between the A layer and the B layer of the multilayer structure was measured as follows. The obtained multilayer structure was stored in an atmosphere of 23°C and 50% RH, and a 15 mm rectangular piece was prepared the day after production to be used as a measurement sample. Using this measurement sample, the T-type peel strength was measured at a pulling speed of 250 mm / min using an autograph "AGS-H type" manufactured by Shimadzu Corporation in an atmosphere of 23°C and 50% RH. The obtained value (unit: g / 15 mm) was taken as the interlayer adhesive strength between the A layer and the B layer. The interlayer adhesiveness was evaluated based on the following evaluation criteria according to the strength of the interlayer adhesive strength. Judgment criteria A: 500g / 15mm or more B: 400g / 15mm or more and less than 500g / 15mm C: 300g / 15mm or more, less than 400g / 15mm D: Less than 300g / 15mm

[0121] (4) Appearance The appearance of the multilayer structures obtained in the Examples and Comparative Examples was evaluated visually based on the following evaluation criteria. Judgment criteria A: Good appearance with no lines or streaks B: Slight streaks are visible in the film flow direction. C: Streaks are visible in the film flow direction. D: Lines or streaks are observed in the film flow direction.

[0122] (5) Dispersibility (dispersed particle size measurement) The multilayer structures obtained in the examples and comparative examples were cut with a microtome to expose the cross section. The cross section was observed using a scanning electron microscope (SEM) to measure the dispersed particle diameter of the thermoplastic resin in the A layer. The SEM observation was performed using a Hitachi High-Technologies SU8010 with a backscattered electron detector. The dispersed particle diameter was the average value of the measured values ​​at 10 randomly selected points. Judgment criteria A: Less than 0.3 μm B: 0.3 μm or more and less than 0.4 μm C: 0.4 μm or more and less than 0.5 μm

[0123] (6) Oxygen permeability (OTR0) The multilayer structures obtained in the examples and comparative examples were conditioned at 20°C and 65% RH for 5 days, and the oxygen permeability was measured using a MOCON OX-TRAN2 / 20 model manufactured by MOCON under conditions of 20°C and 65% RH in accordance with the method described in JIS K 7126-2 (isobaric method; 2006), and the average value was calculated (unit: mL / (m 2 The oxygen permeability before the bending test described later was set as OTR0. Note that the oxygen permeability was 20 mL / (m 2 ·day·atm) or less, under 1 atmosphere conditions of 1m 2 It was determined that the material had gas barrier properties because the oxygen permeability was less than 20 mL per day. Judgment criteria A: 5.0 mL / m 2 ·day·atm≧OTR0 B: 5.0 mL / m 2 ·day·atm <OTR0≦10.0mL / m 2 ·day·atm C: 10.0 mL / m 2 ·day·atm <OTR0≦20.0mL / m 2 ·day·atm D: 20 mL / m 2 ·day·atm <OTR0

[0124] (7) Bending resistance (gas barrier properties before and after bending (OTR0 / OTR50)) The multilayer structures obtained in the examples and comparative examples were repeatedly bent 50 times in an environment of 23°C using a "BE1006 thermostatic chamber equipped Gelbo Flex Tester" manufactured by Tester Sangyo Co., Ltd. in accordance with ASTM-F392-74. The gas barrier properties before and after bending were evaluated. The oxygen permeability before bending was defined as OTR0, and the oxygen permeability after bending was defined as OTR50, and OTR0 / OTR50 was evaluated based on the following criteria. Judgment criteria A: OTR0 / OTR50≧0.9 B:0.9>OTR0 / OTR50≧0.8 C:0.8>OTR0 / OTR50≧0.7 D:0.7>OTR0 / OTR50

[0125] (8) Recycling test (torque behavior) 60 g of the multilayer structures obtained in the Examples and Comparative Examples were cut (approximately 1 cm x 1 cm) to fit the inlet of a Labo Plastomill (Toyo Seiki Seisakusho's "20R200" biaxial counter-rotation), and kneaded at 60 rpm and 200°C. The torque 5 minutes after the start of kneading was defined as T5, and the torque 60 minutes after the start of kneading was defined as T60, and T60 / T5 was evaluated based on the following criteria. The smaller the T60 / T5, the smaller the viscosity change, the better the long-run properties, and the easier it is to recycle. Judgment criteria A: 1.1≧T60 / T5 B: 1.5≧T60 / T5>1.1 C:2.0≧T60 / T5>1.5 D:T60 / T5>2.0

[0126] <Example 1> 90 parts by mass of EVAL (registered trademark) E105B (EVOH-1) and 10 parts by mass of Scona TPPP2112GA (a2-1) were dry blended, and melt pelletized at a screw speed of 100 rpm and discharge of 6.5 kg / hr in a twin-screw extruder (diameter 25 mm, L / D = 25) manufactured by Toyo Seiki Seisakusho Co., Ltd. to produce an EVOH composition. The obtained EVOH composition and Estane 2103-90AE (TPU-1) were used as materials, and fed in a molten state at 190 ° C to a co-extruder having a 19-layer feed block and co-extruded to produce a multilayer structure with a total of 19 layers in which 9 EVOH layers (A layers) and 10 TPU layers (B layers) were alternately laminated.

[0127] The cross-section of the multilayer structure was observed using a DIGITAL MICROSCOPE VK-X200 manufactured by KEYENCE Corporation, and the average thickness of each layer A (gas barrier layer) was 1.1 μm, and the average thickness of each layer B (TPU layer) was 3.3 μm. Each thickness was the average value of the measurements at 10 randomly selected points.

[0128] The obtained multilayer structure was evaluated according to the above (1) to (8). The evaluation results are shown in Table 1. In the obtained multilayer structure, the interlayer adhesive strength was 730 g / 15 mm, the dispersed particle diameter of the thermoplastic resin (a2) was 0.23 μm, and the OTR0 was 3.0 mL / (m 2 ·day·atm), and the OTR50 is 3.2mL / (m 2 ·day·atm), OTR0 / OTR50 was 0.94, and in the recycling test, T5 was 6.72 N·m, T60 was 6.82 N·m, and T60 / T5 was 1.0.

[0129] In addition, the multilayer structure obtained in Example 1 was embedded in epoxy resin, and a transverse section was prepared using an ultramicrotome. The obtained transverse section was stained with solid osmium oxide for 5 days in a gas phase, and observed at a magnification of 5000 times using a transmission electron microscope (TEM) "JEM2100" manufactured by JEOL Ltd. The TEM image of the observed cut surface of the A layer is shown in FIG. 1. It was confirmed that the EVOH (a1) was stained gray or black, and that the EVOH (a1) was dispersed in a dotted manner in the dispersed particles of the thermoplastic resin (a2). The dispersed particle diameter of the EVOH (a1) in the dispersed particles of the thermoplastic resin (a2) was 0.05 μm, which was the average value of the measurements at 10 randomly selected points.

[0130] <Examples 2 to 30 and Comparative Examples 1 to 4> Except for the changes shown in Tables 1 to 3, the multilayer structure was used and evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 to 3. Tables 1 to 3 also show the MFR (melt flow rate) of each thermoplastic resin (a2) used.

[0131] [Table 1]

[0132] [Table 2]

[0133] [Table 3]

[0134] As shown in Tables 1 to 3, Examples 1 to 30 have good solvent resistance (resistance to interlayer peeling after immersion in an organic solvent), gas barrier properties, and flex resistance. Furthermore, Examples 1 to 30 also have good interlayer adhesion, appearance, dispersibility, and recyclability. In addition, when comparing Examples 7 to 9, which are the same except for the presence or absence of a metal salt, it is found that the addition of a metal salt to Layer A improves interlayer adhesion and recyclability.

[0135] On the other hand, Comparative Example 1, in which the thermoplastic resin (a2) was not contained in the A layer, had poor solvent resistance, and Comparative Example 2, in which the content of the thermoplastic resin (a2) in the A layer was too high, had poor gas barrier properties, interlayer adhesion, and recyclability. In Comparative Example 3, in which the total number of layers of the A layer and the B layer was small, the solvent resistance was sufficient, but the bending resistance was poor. In addition, when Comparative Example 1 (19 layers) and Comparative Example 4 (3 layers), which differ only in the number of layers, are compared, the solvent resistance of Comparative Example 1 was D, while the solvent resistance of Comparative Example 4 was C. In other words, it can be seen that interlayer peeling after immersion in an organic solvent is a phenomenon that occurs significantly when the number of layers is large.

[0136] <Example 31> A laminate was produced in the same manner as in Example 1, except that the average thickness of the layer corresponding to the polyurethane layer (B1) was adjusted to 3.3 μm, and the average thickness of the layer corresponding to the polyurethane layer (B2) was adjusted to 20 μm. The interlayer adhesive strength of the obtained laminate was 750 g / 15 mm, the dispersed particle diameter of the thermoplastic resin (a2) in the A layer was 0.23 μm, and the OTR0 was 3.0 mL / (m 2 ·day·atm), and the OTR50 is 3.1mL / (m 2 The mechanical properties of the polymer were as follows: T5 was 10.51 N m, T60 was 10.75 N m, and T60 / T5 was 1.02 in the recycling test. The solvent resistance, appearance, and dispersibility were also evaluated in the same manner as in Example 1, and all were rated A.

[0137] <Example 32> A laminate was produced and evaluated in the same manner as in Example 31, except that a resin composition having a ratio of TPU-1:EVOH composition produced in Example 1 of 95:5 was used as the protective layer (D) to be directly laminated on the outer side of the polyurethane layer (B2) in Example 31, and two protective layers (D) were provided by coextrusion to produce a laminate having a total of 21 layers. The average thickness per layer of the protective layer (D) was 500 μm. The interlayer adhesion of the obtained laminate was 780 g / 15 mm, the dispersed particle diameter of the thermoplastic resin (a2) in layer A was 0.25 μm, and the OTR0 was 3.0 mL / (m 2·day·atm), and the OTR50 is 3.1mL / (m 2 The average mechanical strength (OTR0 / OTR50) was 18.75 N m, the average mechanical strength (T5) was 18.75 N m, the average mechanical strength (T60) was 18.21 N m, and the average mechanical strength (T60 / T5) was 0.97. The solvent resistance, appearance, and dispersibility were also evaluated in the same manner as in Example 1, and all were rated A. [Industrial Applicability]

[0138] The multilayer structure of the present invention can be used as a material requiring gas barrier properties, durability, stretchability, etc., for example, food packaging materials, medical container packaging materials, other container packaging materials, industrial sheet materials, building sheet materials, agricultural sheet materials, geomembranes, radon barrier films, other sheet materials, various other pipes, etc. In particular, the multilayer structure of the present invention can be suitably used as a material for gas barrier films laminated on membranous rubber products such as tire inner liners, shoe sole air cushion materials, accumulator inner bags, air-filled balls, air springs, etc.

Claims

1. A multilayer structure comprising a gas barrier layer (A) containing an ethylene-vinyl alcohol copolymer (a1) and a thermoplastic resin (a2) having a functional group capable of reacting with the ethylene-vinyl alcohol copolymer (a1), and a polyurethane layer (B) containing a thermoplastic polyurethane (b), wherein the content of the thermoplastic resin (a2) is 0.1 to 30 parts by mass relative to 100 parts by mass of the total of the ethylene-vinyl alcohol copolymer (a1) and the thermoplastic resin (a2), and at least one pair of the gas barrier layer (A) and the polyurethane layer (B) are directly laminated together, the total number of the gas barrier layer (A) and the polyurethane layer (B) is 9 to 300, and the acid value of the thermoplastic resin (a2) is 5 to 50 mgKOH / g. When immersed for 30 minutes in a 40°C liquid obtained by mixing 1-propanol and water in a mass ratio of 60:40, the gas barrier layer (A) has a swelling degree of 30% by mass or less, and the polyurethane layer (B) has a swelling degree of 30% by mass or less.

2. The multilayer structure according to claim 1 , wherein the functional group of the thermoplastic resin (a2) is a carboxy group or a derivative thereof.

3. The multilayer structure according to claim 1 or 2, wherein the thermoplastic resin (a2) is at least one selected from the group consisting of modified polyethylene, modified polypropylene, modified ethylene-vinyl acetate copolymer, and modified ethylene-ethyl acrylate copolymer.

4. The multilayer structure according to any one of claims 1 to 3, wherein the ethylene unit content of the ethylene-vinyl alcohol copolymer (a1) is 20 mol % or more and 60 mol % or less.

5. The multilayer structure according to any one of claims 1 to 4, wherein the gas barrier layer (A) further comprises a higher fatty acid metal salt (a3).

6. 6. The multilayer structure according to claim 1, wherein the gas barrier layers (A) and the polyurethane layers (B) are laminated alternately.

7. The multilayer structure according to claim 6, wherein the polyurethane layer (B) comprises a polyurethane layer (B1) having a gas barrier layer (A) directly laminated on both sides thereof, and a polyurethane layer (B2) having a gas barrier layer (A) directly laminated on only one side thereof.

8. 8. The multilayer structure according to claim 7, comprising a protective layer (D) directly laminated to the polyurethane layer (B2), the protective layer (D) comprising a thermoplastic polyurethane (x).

9. 9. The multilayer structure of claim 8, wherein the protective layer (D) comprises an ethylene-vinyl alcohol copolymer (y).

10. The multilayer structure according to claim 8 or 9, wherein the average thickness of each protective layer (D) is 300 μm or more and 800 μm or less.

11. The multilayer structure according to any one of claims 1 to 10, wherein the average thickness of each gas barrier layer (A) is from 0.1 µm to 15 µm.

12. The multilayer structure according to any one of claims 1 to 11, wherein the average thickness of each polyurethane layer (B) is from 0.1 µm to 30 µm.

13. The multilayer structure according to any one of claims 1 to 12, wherein the gas barrier layer (A) forms a phase-separated structure having a sea phase and an island phase, the sea phase contains an ethylene-vinyl alcohol copolymer (a1), and the island phase contains a thermoplastic resin (a2).

14. The multilayer structure according to claim 13, further comprising a phase containing an ethylene-vinyl alcohol copolymer (a1) inside the island phase.

15. A molded article comprising the multilayer structure according to any one of claims 1 to 14, wherein at least one of the gas barrier layer (A) and the polyurethane layer (B) contains a colorant.

16. A method for producing a molded article, comprising a step of contacting the multilayer structure according to any one of claims 1 to 14 with a treatment liquid containing an organic solvent.

17. The method for producing a molded article according to claim 16 , wherein the treatment liquid contains a colorant.

Citation Information

Patent Citations

  • Gas barrier composite film

    JP2004322602A

  • Multilayer film and flexible container using the film

    JP2006272569A

  • Laminated body, its manufacturing method and tire using it

    JP2008024228A

  • Film, inner liner for tire, and tire using the same

    JP2009263653A

  • Inner liner and tire using the inner liner

    JP2011105066A